Nilai Perusahaan: Apakah Dipengaruhi Green Accounting, Performansi Lingkungan dan Kemampulabaan? - Fania Maulida Pangesti; Shinta Permata Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Firm value is an interpretation of the firm's process from time to time in running the activities from its inception to the present. This study aims to analyse the effect of Green Accounting, Environmental Performance, and Profitability on Firm Value. The population in this study are energy sector companies listed on the Indonesia Stock Exchange in 2021-2023. The sampling technique use a purposive sampling method and obtained a sample of 102 companies that met the criteria. Firm value is measured using Tobin's Q proxy. The research method used is quantitative research. The data source use secondary data in the form of company's annual financial statements. The data analysis technique used is multiple regression analysis with the SPSS 25 program. The results show that environmental performance and profitability effect firm value, while green accounting has no effect on firm value.